Copper-molybdenum lamination etching liquid composition for panel and etching method
By adding organic phosphonic acid containing hydroxyl and/or amino group-substituted carbon atoms to the copper-molybdenum laminate etching solution, the CD-Loss and undercut problems in copper-molybdenum laminate etching is solved, and the wiring accuracy and product quality stability are improved.
Patent Information
- Application Number
- CN202411725984.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
AI Technical Summary
In high-generation panels, the inclination angle of CD-Loss and metal wire etching caused by electrochemical reactions during copper and molybdenum stacking is too large, and the molybdenum layer bottoming problem is serious during over-cutting, which affects wiring accuracy.
By adding organic phosphonic acid containing hydroxyl and/or amino substituted carbon atoms to the copper-molybdenum laminated etching solution composition, the potential difference between copper and molybdenum is optimized, and the undercut problem caused by overcut is improved.
It effectively reduces the occurrence of molybdenum layer undercutting time, improves wiring accuracy, and increases the margin to meet different CD-loss numerical requirements.
Smart Images

Figure CN119663281A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-molybdenum etching solutions, and in particular to a copper-molybdenum laminated etching solution composition for a panel and an etching method. Background Art
[0002] In order to reduce impedance and improve electrical properties, copper wiring is usually used in high-generation panels. However, copper has poor adhesion to glass film and silicon, and in order to prevent Cu diffusion from the silicon layer, molybdenum or its alloy is usually used as a barrier metal.
[0003] During the wet etching of copper-molybdenum stacks using copper-molybdenum etching liquid, copper and molybdenum produce electrochemical reactions at the overlapping surfaces. Since copper has a higher potential than molybdenum, the etching speed of copper is much faster than that of molybdenum, which leads to excessive CD-Loss (line width change before and after etching) and excessive metal line etching inclination. One way to reduce the etching speed difference is to add nitrogen azoles as electrochemical inhibitors to improve the line width change and etching inclination.
[0004] Based on some special production requirements, such as the thickness of the molybdenum layer or molybdenum alloy layer is about 300 angstroms, the thickness of the copper layer is more than 3000 angstroms, and the CD-Loss is controlled at a predetermined larger value, such as more than 0.9 microns, it is necessary to further extend the etching time on the basis of completing the etching, that is, over-etching. It is found in the experiment that over-etching will cause undercutting problems in the molybdenum layer or molybdenum alloy layer, and as the etching time increases, the undercutting situation will worsen, thereby leading to the degradation of wiring accuracy.
[0005] In addition, there is an allowable deviation in the thickness of the metal plating at various locations in larger-sized high-generation panels. During wet etching, the etching time is shorter in areas where the copper layer is thinner. Therefore, the over-etching amount of the same panel under the same wet etching time varies, and the difficulty of controlling the undercut defect of the entire panel increases accordingly. Summary of the invention
[0006] One of the purposes of the present invention is to overcome the defects existing in the prior art and provide a copper-molybdenum laminate etching solution composition for a panel, which improves the undercutting problem of the molybdenum layer caused by a larger CD-Loss etching requirement by adding an organic phosphonic acid containing hydroxyl and / or amino substituted carbon atoms, thereby improving the wiring accuracy.
[0007] In order to achieve the above technical effects, the technical solution of the present invention is: a copper-molybdenum laminate etching solution composition for a panel, comprising, by mass percentage: 5% to 20% hydrogen peroxide, 5% to 13% organic carboxylic acid, 5% to 13% organic base, 0 to 0.4% electrochemical copper inhibitor, 0 to 2% hydrogen peroxide stabilizer, 0 to 0.4% organic phosphonic acid containing hydroxyl and / or amino substituted carbon atoms, and 50% to 83% deionized water.
[0008] Furthermore, the copper-molybdenum stack etching solution composition for the panel includes: 6% to 16% hydrogen peroxide, 5% to 10% organic carboxylic acid, 5% to 10% organic base, 0 to 0.3% electrochemical copper inhibitor, 0 to 1.5% hydrogen peroxide stabilizer, 0 to 0.2% organic phosphonic acid containing hydroxyl and / or amino substituted carbon atoms, and 55% to 80% deionized water.
[0009] A preferred technical solution is that the organic phosphonic acid is at least one selected from hydroxyethylidene diphosphonic acid, 2-hydroxyphosphonoacetic acid, ethylenediaminetetramethylenephosphonic acid, diethylenetriaminepenta(methylenephosphonic acid), and aminotri(methylenephosphonic acid); further, the organic phosphonic acid is hydroxyethylidene diphosphonic acid and / or 2-hydroxyphosphonoacetic acid.
[0010] A preferred technical solution is that the organic carboxylic acid is at least one of malonic acid, succinic acid and α-hydroxy acid; further, the organic carboxylic acid is α-hydroxy dicarboxylic acid.
[0011] A preferred technical solution is that the organic base is at least one selected from monoethanolamine, diethanolamine, triethanolamine, triisopropanolamine, diisopropanolamine, isopropanolamine, and 3-diethylaminopropylamine.
[0012] A preferred technical solution is that the electrochemical copper inhibitor is a nitrogen azole copper inhibitor.
[0013] A preferred technical solution is that the hydrogen peroxide stabilizer is at least one selected from phenyl urea, allyl urea, and thiourea.
[0014] A preferred technical solution is that the etching solution composition does not contain fluoride ions.
[0015] A preferred technical solution is that the mass percentage of the organic phosphonic acid in the etching solution composition is 0-0.2%; further, the mass percentage of the organic phosphonic acid in the etching solution composition is 0-0.08%; further, the mass percentage of the organic phosphonic acid in the etching solution composition is 0.005%-0.05%.
[0016] The second object of the present invention is to provide an etching method, based on the above-mentioned copper-molybdenum multilayer etching liquid composition for panel, using the copper-molybdenum multilayer etching liquid composition for panel to wet-etch a workpiece, the workpiece comprising a substrate, a molybdenum layer plated on the surface of the substrate, a copper layer plated on the molybdenum layer away from the surface of the substrate, and a patterned photoresist layer formed on the surface of the copper layer away from the molybdenum layer.
[0017] A preferred technical solution is that the process temperature of the wet etching is 28-38°C; further, the process temperature of the wet etching is 30-35°C.
[0018] The advantages and beneficial effects of the present invention are:
[0019] The panel copper-molybdenum laminate etching solution composition for panels optimizes the potential difference between copper and molybdenum by adding a predetermined content of organic phosphonic acid containing hydroxyl and / or amino substituted carbon atoms together with an electrochemical copper inhibitor, thereby improving the undercut problem caused by the increase of overetching time;
[0020] There is no obvious undercut problem after the etching time is controlled to be longer, which makes it easier to meet different CD-loss value requirements by extending the etching time, thereby increasing the margin for ensuring the quality of etching products;
[0021] It is helpful to reduce the undercut defect rate caused by uneven film thickness under the same wet etching time of the same panel. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the etched cross section of the comparative example 1OE30% panel;
[0023] Figure 2 This is the SEM image of the etched cross section of the comparative example 1OE50% panel;
[0024] Figure 3 This is the SEM image of the etched cross section of the comparative example 1OE70% panel;
[0025] Figure 4 is an etched cross-sectional SEM image of the OE30% panel of Example 5;
[0026] Figure 5 is an etched cross-sectional SEM image of the OE50% panel of Example 5;
[0027] Figure 6 is an SEM image of an etched cross section of the OE70% panel of Example 5;
[0028] Figure 7 is an SEM image of an etched cross section of the OE100% panel of Example 5;
[0029] Figure 8 is an etched cross-sectional SEM image of the OE30% panel of Example 5;
[0030] Fig. 9 is an etched cross-sectional SEM image of the OE50% panel of Example 5;
[0031] Fig.10 is an SEM image of an etched cross section of the OE70% panel of Example 5;
[0032] Fig.11 This is a SEM image of the etched cross section of the OE100% panel of Example 5. DETAILED DESCRIPTION
[0033] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0036] The substitution of a carbon atom with a hydroxyl group and / or an amino group means that a hydrogen atom of the carbon atom is substituted with a hydroxyl group and / or an amino group.
[0037] Hydrogen peroxide is used as the oxidizing agent for copper.
[0038] The organic carboxylic acid reacts with copper oxide, so that copper ions enter the etching solution, and has the effect of modifying the etching cross-sectional morphology, which can make the etching cross-sectional morphology smoother. The organic carboxylic acid can be selected from one or a combination of two or more of malonic acid, succinic acid, glycolic acid, malic acid, citric acid, lactic acid, isocitric acid, maleic acid, glutamic acid, glycine, alanine, aminosuccinic acid or tartaric acid. Further, α-hydroxy acids include glycolic acid, lactic acid, malic acid, tartaric acid and citric acid. Further, α-hydroxy dicarboxylic acids include malic acid and tartaric acid.
[0039] The main function of the organic base is to adjust the pH of the etching solution composition system, slow down the decomposition of hydrogen peroxide, improve the stability of the etching solution and extend its service life. The organic base can be selected from one or a combination of two or more of isopropanolamine, trichloromelamine, dimethylethanolamine, triethanolamine, diethanolamine, monoethanolamine, diisopropanolamine, triisopropanolamine, 3-diethylaminopropylamine, tetramethylammonium hydroxide, diethylaminopropylamine, ethylenediamine, diethylamine, propylenediamine, butylene diamine, 2-hydroxybutylene diamine, N,N-dihydroxyethylbutylene diamine, N,N-diaminomethylethylenediamine, N,N-diaminomethylpropylenediamine or N,N-diaminoethylpropylenediamine; more preferably, at least one of diethanolamine, triisopropanolamine, diisopropanolamine, isopropanolamine and 3-diethylaminopropylamine.
[0040] The selection range of electrochemical copper inhibitors includes but is not limited to benzotriazole, 5-methylbenzotriazole, 5-methyltetrazolyl, 1-aminotetrazolyl, 5-mercapto-1-methyltetrazolyl, 5-mercapto-1-dimethylaminoethyl-1H-tetrazolyl, and pentaaminotetrazolyl, and pentaaminotetrazolyl is further preferred.
[0041] The hydrogen peroxide stabilizer is preferably a stabilizer other than the above-mentioned organic acid, organic base, electrochemical copper inhibitor, and organic phosphonic acid, and is preferably at least one selected from phenyl urea, allyl urea, and thiourea.
[0042] In the expression of the mass percentage of a component, 0 to n% does not include the minimum value 0 and includes the maximum endpoint value n%.
[0043] The following chemicals used in the examples were all commercially available of analytical grade.
[0044] Hydrogen peroxide: Add 31% hydrogen peroxide to the etching solution;
[0045] Organic carboxylic acids: succinic acid, glycolic acid, malic acid, tartaric acid;
[0046] Organic base: diethanolamine, 3-diethylaminopropylamine;
[0047] Hydrogen peroxide stabilizer: phenyl urea;
[0048] Electrochemical copper inhibitor: pentaaminotetrazolyl;
[0049] Organic phosphonic acid: hydroxyethylidene diphosphonic acid, 2-hydroxyphosphonoacetic acid, ethylenediaminetetramethylenephosphonic acid;
[0050] Solvent: deionized water.
[0051] 1. Configure the etching panel
[0052] Using glass as a substrate, a molybdenum layer with a thickness of 300 angstroms and a copper layer with a thickness of 4000 angstroms are plated in sequence, and a patterned photoresist layer is coated, exposed, and developed on the copper layer in sequence.
[0053] 2. The copper-titanium etching solution composition for liquid crystal panels of the embodiment and the comparative example is configured according to the following table:
[0054] 1. Regarding the embodiments and comparative examples of organic phosphonic acid, embodiments 1-3 and comparative examples 1-2 are configured according to the following table:
[0055]
[0056] 3. Copper-Molybdenum Stack Etching
[0057] After preliminary etching experiments (the etching temperature of the panel copper-molybdenum laminated etching solution composition is 33°C), the etching time of the panel is determined, and the panel is etched according to the time of OE30%, OE50%, OE70%, and OE100% (example). After reaching the predetermined etching time, the panel is taken out of the etching solution, rinsed with pure water for 30s, and blown dry with a nitrogen gun.
[0058] 4. Panel etching effect detection
[0059] The etched panel was observed by scanning electron microscope to obtain the CD-loss and molybdenum layer undercut (NG / OK) of Examples 1-3 and Comparative Examples 1-2, as shown in the following table:
[0060]
[0061] Examples 1-3 and Comparative Examples 1-2: When succinic acid is used as the organic carboxylic acid component, hydroxyethylidene diphosphonic acid is added to the panel copper-molybdenum laminated etching solution composition, and the OE50% molybdenum layer undercut meets the qualified requirements; the panel copper-molybdenum laminated etching solution composition OE50% molybdenum layer undercut that does not contain hydroxyethylidene diphosphonic acid does not meet the qualified requirements; the phosphate triammine phosphate in Comparative Example 2 has no obvious effect on improving the over-cutting problem.
[0062] Example 1-3: As the mass percentage of hydroxyethylidene diphosphonic acid in the panel copper-molybdenum laminate etching solution composition increases, the over-etching CD-loss increases and the increase rate gradually slows down, and the effect of improving the over-etching undercut problem is equivalent.
[0063] 2. Regarding the examples of organic phosphonic acid and organic carboxylic acid, Examples 1-3 and Comparative Examples 1-2 are configured according to the following table:
[0064]
[0065] The etched panel was observed by scanning electron microscope to obtain the CD-loss and molybdenum layer undercut conditions (NG / OK) of Examples 4-6, as shown in the following table:
[0066]
[0067] Example 1, Example 4-6: When succinic acid and glycolic acid are used as organic carboxylic acids, the etching speed is faster and the over-etching CD-loss is larger; malic acid and tartaric acid in Examples 5 and 6 are more conducive to obtaining a larger CD-loss, the undercut of the molybdenum layer meets the qualified requirements, and the amount of hydroxyethylidene diphosphonic acid added is small.
[0068] 3. Regarding the specific selected examples of organic phosphonic acid, Examples 7 and 8 are configured according to the following table:
[0069] Components Example 7 Example 8 Hydrogen Peroxide 10% 10% Organic carboxylic acid Malic Acid 7.5% Malic Acid 7.5% Diethanolamine 8% 8% Phenylurea 0.1% 0.1% Pentaaminotetrazolyl 0.02% 0.02% Organic phosphonic acid 2-Hydroxyphosphonoacetic acid 0.02% Ethylenediaminetetramethylenephosphonic acid 0.02% Deionized water margin margin
[0070] The etched panel was observed by scanning electron microscope to obtain the CD-loss and molybdenum layer undercut conditions (NG / OK) of Examples 7 and 8, as shown in the following table:
[0071]
[0072] Examples 5, 7, and 8: When hydroxyethylidene diphosphonic acid and 2-hydroxyphosphonoacetic acid are used as organic phosphonic acids, the improvement effect on the undercut of the molybdenum layer is better than that of ethylenediaminetetramethylenephosphonic acid in Example 8, and 2-hydroxyphosphonoacetic acid is conducive to obtaining a larger CD-loss, which can meet the copper-molybdenum stack etching requirements with a larger CD-loss, and has stronger compatibility.
[0073] 4. Regarding the embodiments of the etching solution composition, embodiments 9 and 10 are configured according to the following table:
[0074] Components Example 9 Example 10 Hydrogen Peroxide 8% 11% Organic carboxylic acid Malic Acid 8% Malic Acid 7% 3-Diethylaminopropylamine 6% 5% Phenylurea 0.1% 0.1% Pentaaminotetrazolyl 0.02% 0.02% Organic phosphonic acid Hydroxyethylidene diphosphonic acid 0.02% Hydroxyethylidene diphosphonic acid 0.02% Deionized water margin margin
[0075] The etched panel was observed by scanning electron microscope to obtain the CD-loss and molybdenum layer undercut conditions (NG / OK) of Examples 9 and 10, as shown in the following table:
[0076]
[0077] Examples 9 and 10: The concentrations of hydrogen peroxide, organic carboxylic acid and organic amine are adjusted within the preferred range, and CD-loss fluctuates within a certain range, both of which meet the qualified requirements for copper-molybdenum stack etching.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A copper-molybdenum laminate etching solution composition for a panel, characterized in that: Calculated by mass percentage, it includes: 5% to 20% hydrogen peroxide, 5% to 13% organic carboxylic acid, 5% to 13% organic base, 0 to 0.4% electrochemical copper inhibitor, 0 to 2% hydrogen peroxide stabilizer, 0 to 0.4% organic phosphonic acid containing hydroxyl and / or amino substituted carbon atoms, and 50% to 83% deionized water.
2. The copper-molybdenum laminate etching solution composition for panels according to claim 1, characterized in that: The organic phosphonic acid is at least one selected from hydroxyethylidene diphosphonic acid, 2-hydroxyphosphonoacetic acid, ethylenediaminetetramethylenephosphonic acid, diethylenetriaminepenta(methylenephosphonic acid), and aminotri(methylenephosphonic acid); further, the organic phosphonic acid is hydroxyethylidene diphosphonic acid and / or 2-hydroxyphosphonoacetic acid.
3. The copper-molybdenum laminated etching solution composition for panels according to claim 1, characterized in that: The organic carboxylic acid is at least one of malonic acid, succinic acid and α-hydroxy acid; further, the organic carboxylic acid is α-hydroxy dicarboxylic acid.
4. The copper-molybdenum laminated etching solution composition for panels according to claim 1, characterized in that: The organic base is at least one selected from monoethanolamine, diethanolamine, triethanolamine, triisopropanolamine, diisopropanolamine, isopropanolamine, and 3-diethylaminopropylamine.
5. The copper-molybdenum laminated etching solution composition for panels according to claim 1, characterized in that: The electrochemical copper inhibitor is a nitrogen azole copper inhibitor.
6. The copper-molybdenum laminated etching solution composition for panels according to claim 1, characterized in that: The hydrogen peroxide stabilizer is at least one selected from phenylurea, allyl urea and thiourea.
7. The copper-molybdenum laminated etching solution composition for panels according to claim 1, characterized in that: The etching solution composition does not contain fluoride ions.
8. The copper-molybdenum laminated etching solution composition for panels according to claim 1, characterized in that: The mass percentage of the organic phosphonic acid in the etching solution composition is 0-0.2%; further, the mass percentage of the organic phosphonic acid in the etching solution composition is 0-0.08%; further, the mass percentage of the organic phosphonic acid in the etching solution composition is 0.005%-0.05%.
9. An etching method, characterized in that: Based on the copper-molybdenum multilayer etching liquid composition for panels described in any one of claims 1 to 8, the copper-molybdenum multilayer etching liquid composition for panels is used to wet-etch a workpiece, wherein the workpiece comprises a substrate, a molybdenum layer plated on the surface of the substrate, a copper layer plated on the molybdenum layer and facing away from the surface of the substrate, and a patterned photoresist layer formed on the surface of the copper layer facing away from the molybdenum layer.
10. The etching method according to claim 9, characterized in that: The process temperature of the wet etching is 28-38°C; further, the process temperature of the wet etching is 30-35°C.